2020 International Workshop on Rapid System Prototyping (RSP) 2020
DOI: 10.1109/rsp51120.2020.9244863
|View full text |Cite
|
Sign up to set email alerts
|

Hardware-in-the-loop simulation with dynamic partial FPGA reconfiguration applied to computer vision in ROS-based UAV

Abstract: Hardware in the loop simulation has become a fundamental tool for the safe and rapid development of embedded systems. Dynamically and partially reconfigurable FPGA provide an energy efficient solution for high performance computing in embedded systems, such as computer vision, with limited resources. Finally 3D simulation with realistic physics simulation is required by designers of Unmanned Aerial Vehicle (UAV) and related missions. The combination of the three techniques are required to design UAV with recon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 18 publications
0
6
0
Order By: Relevance
“…The flight controller was implemented as an overlay based on the PYNQ project. In 2020, Moreac et al [23] proposed FPGA based computer vision for drones by hardware-in-the-loop simulation. Finally in 2021 at our research group, Kövari [24] demonstrated the use of FPGA accelerated deep learning inference for autonomous drone navigation, also based on PYNQ.…”
Section: Related Workmentioning
confidence: 99%
“…The flight controller was implemented as an overlay based on the PYNQ project. In 2020, Moreac et al [23] proposed FPGA based computer vision for drones by hardware-in-the-loop simulation. Finally in 2021 at our research group, Kövari [24] demonstrated the use of FPGA accelerated deep learning inference for autonomous drone navigation, also based on PYNQ.…”
Section: Related Workmentioning
confidence: 99%
“…Additionally, none of the methods have been demonstrated to run onboard a UAV in real-time. Because of their power efficiency and high throughput capability, FPGAs have been used on UAVs as flight controllers [40], neural network accelerators [41], [42], and generally deployed for their reconfigurability [43], [44]. NASA's Mars UAV [45] uses FPGAs for flight control, fault tolerance, and as IO and communications hubs.…”
Section: Related Workmentioning
confidence: 99%
“…NASA's Mars UAV [45] uses FPGAs for flight control, fault tolerance, and as IO and communications hubs. FPGAs have also shown great promise for embedded, real-time implementations of advanced algorithms such as linear and nonlinear Model Predictive Control (MPC) [46], [47], [48] and various computer vision algorithms [44], [49]. Ladig et al [50] show an FPGA-accelerated perception system that assists a pilot in yaw-alignment of a drone relative to detected lines.…”
Section: Related Workmentioning
confidence: 99%
“…As an example of this proposed new architecture, we have started the development and test of dynamically reconfigurable hardware. We use ROS and interface it with the FPGA to take advantage of partially and dynamically reconfigurable hardware [ 124 ]. Such a complex system can only be developed by combining efforts and contributions from the research community.…”
Section: Addressing the Computational Gap For High Levels Of Autonmentioning
confidence: 99%